Flutter analysis of supersonic wing with external stores - Abdullah, Nur Azam; Sulaeman, Erwin (2013)
One of the most dangerous aeroelastic failure phenomenon is flutter. The flutter characteristic is different for each type of aircraft depends on the wing geometry and its operational region of subsonic, transonic or supersonic. Prior to performing flight flutter test, extensive numerical simulations and Ground Vibration Test should be conducted where the structural finite element modes and the experimentation results should be matched otherwise the numerical simulation model could be rejected. In the present paper, the simulation of supersonic wing equipped with external loads of missiles on the wing had been analyzed at high supersonic region. The structural mode shapes at each generated frequency mode are also visually presented. The analysis is carried out using FEM software of MSC Nastran. The wing flutter with the external stores had been simulated at different altitudes. The result shows that the flutter velocity is sensitive to the flight altitude. For this reason, the flutter analysis is conducted also for a negative altitude. The negative altitude is obtained by considering the constant equivalent speed-Mach number rule at flutter speed boundary as a requirement in standard regulation of transport aircraft.